Issues of Jurisprudential Principles: Between Certainty and Presumption - A Study on the Cause of Disagreement - Mohammed Ali M. Alasmari; Musallam Bakheet M Aljohani (Kurdish Studies, 2024)
This research addresses the reason for the disagreement on the issue of the definiteness or presumptiveness of the principles of Islamic jurisprudence. The concept of "the cause of foundational disagreement" among scholars has been defined, and the paper delves into the definitions of certainty (al-qat') and presumption (al-zann). Subsequently, the locus of disagreement on the issue was elucidated, revealing two schools of thought: those who consider the issues of the principles of jurisprudence to be definitive, and those who view some as definitive and others as presumptive. The paper then elucidates the reasons for the disagreement, which are based on two factors: firstly, the disagreement over the subject matter of the principles of jurisprudence, and secondly, the disagreement over the derivation of principles of jurisprudence. The research concludes with several recommendations, including the importance of studying the reasons for disagreement in foundational issues, elucidating the connection between them, emphasizing the significance of understanding and applying the foundational rules in interpreting and judging Sharia rulings, and underscoring the necessity of comprehending the principles of jurisprudence as a mediator between beliefs and Sharia rulings to clarify the evidence and concepts. God grants success.